Effects of aerobic exercise on blood glucose levels and lipid profile in Diabetes Mellitus type 2 subjects - Jyotsna Aggarwala; Shipra Sharma; Saroochi; Ajay Jain; Aparna Sarkar (Al Ameen Journal of Medical Sciences, 2016)
Introduction and Background: Diabetes mellitus is a metabolic disorder resulting from defective insulin secretion, insulin action, or both. A consequence of this is chronic hyperglycaemia with disturbances of carbohydrates, proteins and fat metabolism. Exercise plays a major role in the prevention and control of insulin resistance, type II diabetes, and diabetes-related health complications. Both aerobic and resistance training improve insulinaction and can assist with the management of blood glucose levels, lipids, blood pressure, cardiovascular risk, mortality, and quality of life. Aims: Effects of aerobic exercise on blood glucose level and lipid profile in Type 2 diabetes mellitus subjects. Materials& Methods: Sedentary men and women suffering from Type II diabetes mellitus (n=20) were selected randomly for this study. Subjects were made to do aerobic exercises for 4 days/week for 30 min duration. They were made to do stepping at a stepper of 9 inches height for first 10 minutes. This was followed by 20 minutes of cycling at the resistance of 5 (according to the static cycle used). The heart rate of the subjects was monitored during the exercises. Blood glucose level and lipid profile were measured biochemically. HbA1c was also checked before and after exercise protocol. Results: Very high density lipoprotein (VLDL) and triglycerides (TG) parameter in lipid profile showed significant decrease as p values were less than <0.001 and <0.05 respectively. Blood glucose levels did not show any significant changes when compared between pre-test and post test values. Discussion and Conclusion: We concluded four weeks of aerobic training significantly decreases VLDL and triglycerides of lipid profile but the changes in other lipid profile parameters i,e, high density lipoprotein (HDL), low density lipoprotein (LDL) Chylomicrons were not significant (p>0.05) .The changes in the glycaemic control and HbA1c were also insignificant (p>0.05). We concluded that duration of 4 weeks aerobic exercise on Type II diabetic patients to improve their glycaemic control and lipid profile was not sufficient as it showed significant changes only in the VLDL and triglycerides parameter of lipid profile.